20(S)-Ginsenoside Rh2-induced apoptosis and protective autophagy in cervical cancer cells by inhibiting AMPK/mTOR pathway. Issue 1 (29th October 2021) - Bian, Shuai; Liu, Meichen; Yang, Song; Lu, Shuyan; Wang, Siming; Bai, Xueyuan; Zhao, Daqing; Wang, Jiawen
ABSTRACT: 20(S)-Ginsenoside Rh2 (GRh2) has various biological activities including anticancer effects. However, no reports have investigated the connection between autophagy and apoptosis in HeLa cells treated with 20(S)-GRh2. In this study, we found that 20(S)-GRh2 suppressed proliferation and induced apoptosis in HeLa cells by activating the intrinsic apoptotic pathway and causing mitochondrial dysfunction. 20(S)-GRh2 enhanced cell autophagy through promoting the phosphorylation of AMPK, depressed the phosphorylation of AKT, and suppressed mTOR activity. Furthermore, treatment with the autophagy inhibitor 3-methyladenine (3-MA) enhanced 20(S)-GRh2-induced apoptosis, while the autophagy inducer rapamycin promoted cell survival. Moreover, the apoptosis inhibitor Z-VAD-FMK significantly restrained the apoptosis and autophagy induced by 20(S)-GRh2 in HeLa cells. We found that 20(S)-ginsenoside Rh2-induced protective autophagy promotes apoptosis of cervical cancer cells by inhibiting AMPK/mTOR pathway. Graphical Abstract: